Variasi Kandungan Merkuri (Hg) Pada Berbagai Macam Bedak Whitening Yang Dijual Pasar Blauran Surabaya - Nastiti Kartikorini (Universitas Muhammadiyah Surabaya, 2018)
Mercury is widely used in cosmetics to remove black spots on the face. Mercury in the smallest amount can be a toxic such as skin discoloration, black spots, allergies and irritation. High doses of mercury can cause permanent damage to the brain, kidneys and impaired development of the fetus,distruction skin surface.The purpose of this study was to analyze mercury levels in various brands of whitening powder sold in Blauran market, Surabaya. The samples were 22 types of whitening powder. The samples were analyzed by Atomic Absorption Spectrophotometer (AAS).According to the results of research on mercury content (Hg) of 22 whitening powder, it is known that 4 whitening powder contain mercury (Hg), and have mercury (Hg) which is vary from the highest level (0.016 ppm) and the lowest level (0,008 ppm). However, the mercury content (Hg) is still below the maximum limit set. Keywords: Whitening Powder, Mercury, Atomic Absorption Spectrophotometer (AAS)